Effects of Taekwondo training on thigh muscle cross-sectional area, health-related physical fitness, HbA1c, and GLP-1 in sedentary older women - Jaehyun Park; Bongjo Kim; Minki Jeong; Hyun-Hun Jung; Garam Hong; Sang Kab Park (Frontiers in Sports and Active Living)
BackgroundSedentary lifestyles in older individuals are associated with reduced physical function and an increased risk of metabolic diseases such as type 2 diabetes. Physical exercise can enhance muscle mass, insulin sensitivity, and metabolic health. Taekwondo, a martial art that integrates both aerobic and resistance components, may improve strength, balance, and metabolic health in older individuals. This study investigated the effect of long-term Taekwondo training on thigh muscle cross-sectional area, health related physical fitness, and metabolic indicators in sedentary older women.MethodsSeventeen participants (aged 65 years and older, sedentary time 8 h and more per day) were randomly assigned to a Taekwondo group (n = 9) and a control group (n = 8). Outcomes, including thigh muscle cross-sectional area, health-related physical fitness, Homeostatic Model Assessment for Insulin Resistance (HOMA-IR), and Glucagon-like peptide-1 (GLP-1) were measured before and after the Taekwondo program. The Taekwondo group underwent 60 min of training, three times per week for 12 weeks. Variable changes over time and between groups were analyzed using two-way repeated measures ANOVA performed for significant interactions.ResultsThe Taekwondo group exhibited a significant reduction in body weight, body mass index, body fat, and mean arterial blood pressure (p < 0.05), as well as increased thigh muscle cross-sectional area, lean body mass and lower limb muscle mass (p < 0.05). Improvements in balance and gait speed, stride were observed (p < 0.05), indicating reduced fall risk and enhanced mobility. Laboratory analyses revealed reduced triglyceride and free fatty acids and elevated HDL-cholesterol and GLP-1 levels (p < 0.05). Increased thigh muscle cross-sectional area was inversely correlated with fasting glucose, insulin, and HOMA-IR, suggesting improved insulin sensitivity and glucose regulation.ConclusionLong-term Taekwondo training improved thigh muscle cross-sectional area, health-related physical fitness and insulin resistance markers in sedentary older women, providing evidence for its use as an effective intervention to promote metabolic health in this population.